Using Local Sámi Culture and History to Teach Pupils about Democracy - Lisbeth Bergum Johanson (University of Aberdeen, School of Education, 2018)
The aim of this study was to investigate how the use of Sámi local culture and history can promote pupils' democratic education. Teachers in the local community were interviewed because they provided information about how place and region create good opportunities for the use of local history as well as history of the Sámi's with the aim of producing democratic citizens. Analyses of the teachers' different uses of local history such as scientifically, existentially, morally and ideologically in teaching, revealed that local contexts that local history provide can make the past more understandable for the pupils. Local history introduces common practices that enable them to participate in discussions with different and extended presentations of the past. According to the teachers, local history and culture create enthusiasm, participation, understanding, critical thinking and recognition. The teachers also used Sámi culture and history to discuss and integrate democratic values such as equality and diversity. The teachers explicitly used local history to promote local Sámi culture and history, and to build identities and create meaning (in life). Using local history when teaching history can arguably contribute to knowledge about a past that is usable - for instance to produce democratic citizens.